Down to earth : designing for the endgame : in view of the 9th edition of the International Architecture Biennale Rotterdam September 2020 - August 2021 - International Architecture Biennale Rotterdam 2020-2021 : Rotterdam, Netherlands); Brugmans, George (2023)
"Without reservations, DOWN TO EARTH starts from the observation that the climate crisis is a given, and that we are already in over our heads. Can we then still redesign our living environment to ensure a sustainable balance, also with all other life forms? George Brugmans chose energy transition and water management as levers for design research aimed at transformational real-world change. Drought in the Dutch Delta, rising sea levels, the need to stop using natural gas in our homes - these are issues for which we urgently must find solutions that can simultaneously be used as leverage for broader change. Brugmans anchors this research methodologically in the history of the IABR, which in the past years has explored how, as a cultural institution, it could design for results in times of climate crisis. DOWN TO EARTH is a visually rich account of an antitypical biennale in times of pandemic, and also - with essays by George Brugmans and Dirk Sijmons and a dialogue between lecturers and students of the Rotterdam Academy of Architecture and Urban Design - a critical reflection on the position of designers at a time when the anthropogenic climate crisis is forcing humanity into the endgame."--Publisher information.
Additional material available online.
Translated from the original Dutch.
Translation of: Down to earth, ontwerpen voor het eindspel.
Includes bibliographical references.
Keywords: Sustainable architecture; Sustainable buildings -- Design and construction; Architecture durable; Sustainable architecture; Sustainable buildings -- Design and construction